Microstrip Sierpinski carpet antenna design - A. Rahim, Mohamad Kamal; Abdullah, Noorsaliza; Abdul Aziz, Mohd. Zoinol Abidin (2005)
Low cost of fabrication and low profile features of microstrip antennas, attract many researchers to investigate the performance of this antenna in various ways. Today, fractal antenna becomes popular among the researcher because they have a peculiar properties that make them suitable for multiband applications. Fractal technologies allowed us to design miniature antennas and integrate multiple telecommunication services such as cellular (GSM 900 and GSM 1800), wireless LAN, GPS and HiperLAN into a single device. Microstrip Sierpinski carpet antenna is proposed for a multiband operation. The fractal antenna offer solutions for the integration of all this application.